PENGARUH KUALITAS LABA TERHADAP COST OF EQUITY CAPITAL DENGAN ASIMETRI INFORMASI SEBAGAI INTEGRASI VARIABEL INTERVENING DAN MODERATING (STUDI PADA PERUSAHAAN TERDAFTAR DI BEI PERIODE TAHUN 2007-2016) - Hikmah Rizki Lainatus Shifa (PEKBIS, 2018)
This study aims to determine the direct effect of Profit Quality on Cost Of EquityCapital , the direct influence of Profit Quality on Information Asymmetry, DirectInfluence Asymmetry Information on Cost Of Equity Capital , the influence of ProfitQuality through Information Asymmetry against Cost Of Equity Capital andinfluence moderation Asymmetry Information against the relationship between ProfitQuality and Cost Of Equity Capital in Consumer Goods Industry company listed onBEI period 2007-2016. The study was conducted for 1 month, from April 2018. Theobject of this research is a manufacturing company engaged in the field of consumergoods industry listed on the IDX period 2007-2016 as many as 27 companies. Thedata used are secondary data sourced from the financial statements of issuers ofannual financial reports (annual report) for the period 2007 to 2017 obtained fromthe BEI website. Data analysis techniques use path analysis using Smart-PLSsoftware (Partial Least Square) starting from model measurement (outer model),model structure (inner model) and hypothesis testing. The results of testing the firsthypothesis in this study indicate that the Quality of Profit significantly influence theCost Of Equity Capital. The results of the second hypothesis show that there is nosignificant influence between the Quality of Profit on Information Asymmetry.Because the percentage of magnitude of the effect is only 0.04%. Then the resultsof the third hypothesis Asymmetry Information significant effect on Cost of EquityCapital. The magnitude of the effect is a percentage of 1.23%. Further the fourthhypothesis shows that there is no effect of Profit Quality against Cost of EquityCapital through Information Asymmetry. Because the percentage of magnitude ofthe effect is only 0.01%. As well as the results of the fifth hypothesis concluded thatmoderation interactions Asymmetry Information on the Quality of Profit against CostOf Equity Capital. But the percentage of the magnitude of the effect is only 0.41% soit is not enough role in improving the influence of Profit Quality against Cost ofEquity Capital.